2015
DOI: 10.1038/srep14646
|View full text |Cite
|
Sign up to set email alerts
|

Optical Limiting and Theoretical Modelling of Layered Transition Metal Dichalcogenide Nanosheets

Abstract: Nonlinear optical property of transition metal dichalcogenide (TMDC) nanosheet dispersions, including MoS2, MoSe2, WS2, and WSe2, was performed by using Z-scan technique with ns pulsed laser at 1064 nm and 532 nm. The results demonstrate that the TMDC dispersions exhibit significant optical limiting response at 1064 nm due to nonlinear scattering, in contrast to the combined effect of both saturable absorption and nonlinear scattering at 532 nm. Selenium compounds show better optical limiting performance than … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
155
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 262 publications
(176 citation statements)
references
References 43 publications
16
155
0
1
Order By: Relevance
“…For the solution of MoS 2 –PVK in DMF (Figures a and d), the normalized transmittance curve shows a meristic peak on to the laser focal point ( z =0) at the lowest excitation of 50 μJ at λ =532 nm and 100 μJ at λ =1064 nm; this indicates an SA response in this sample. However, a valley within the peak shows up at the focus and deepens gradually with increasing incident pulse energy, which can contribute to the thermally induced nonlinear scattering (NLS) behavior that occurs following SA . In addition, as shown in Figure b and e, the MoS 2 /PVK blends exhibit similar nonlinear responses to that of the solution of MoS 2 –PVK in DMF at λ =532 nm, in contrast to only SA performance at λ =1064 nm.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…For the solution of MoS 2 –PVK in DMF (Figures a and d), the normalized transmittance curve shows a meristic peak on to the laser focal point ( z =0) at the lowest excitation of 50 μJ at λ =532 nm and 100 μJ at λ =1064 nm; this indicates an SA response in this sample. However, a valley within the peak shows up at the focus and deepens gradually with increasing incident pulse energy, which can contribute to the thermally induced nonlinear scattering (NLS) behavior that occurs following SA . In addition, as shown in Figure b and e, the MoS 2 /PVK blends exhibit similar nonlinear responses to that of the solution of MoS 2 –PVK in DMF at λ =532 nm, in contrast to only SA performance at λ =1064 nm.…”
Section: Resultsmentioning
confidence: 95%
“…revealed the size‐dependent NLO properties of thin MoS 2 and other transition‐metal dichalcogenide (TMDC) nanosheets for picosecond pulses at λ =532 nm . Dong and co‐workers reported the prominent OL performances of TMDC nanosheets, including MoS 2 , for nanosecond pulses at λ =532 and 1064 nm . By embedding few‐layer MoS 2 as inclusions in a poly(methyl methacrylate) (PMMA) host, Tao et al.…”
Section: Introductionmentioning
confidence: 99%
“…[28,49] It should be noted that the OL response of MoS 2 -H/CNTsu nder fs regime was slightly better than that of MoS 2 -L/CNTs ( Figure 4), but was slightly worse under the ns regime ( Figure 6). The enhanced NLO performance of the nanocomposites can be mainly ascribed to the possible photoinduced electron transfer and effective coupling between MoS 2 and CNTs.…”
Section: Resultsmentioning
confidence: 96%
“…[14,15] Two-dimensional (2D) materials, such as graphene, transition-metal dichalcogenides (TMDs), topological insulators, and black phosphorus (BP), have been reported to have excellent NLO performances. [25][26][27][28] Nanocomposites of MoS 2 and CNTs have been investigated widelyi na pplications such as energy storagea nd hydrogen evolution. [22][23][24] Compared to graphene with zero-band gap and BP with easy oxidation and deliquenscence, MoS 2 is semiconducting and has good chemical stability.I th as been confirmed that MoS 2 nanosheets have excellent third-order NLO performance over ab road wavelength range from visible( Vis) to near infrared (NIR) region with versatile optical mechanisms, such as saturable absorption (SA), two-photon absorption (TPA), and nonlinear scattering (NLS).…”
Section: Introductionmentioning
confidence: 99%
“…The history of metal halide perovskites dates back to late 1980s, and early studies mainly focused on their peculiar dielectric properties . Since 2009, perovskites (ABX 3 , A = monovalent cation, such as ethylammonium cation, alkali cation; B = bivalent cation, such as Pb 2+ , Sn 2+ ; and X = monovalent anion, such as halide anion) have received great attention as photoactive materials for optoelectronic devices, with the power conversion efficiency (PCE) of perovskite‐based photovoltaic cells being increased from 3.8% to 22.1% in only 7 years . Besides their peculiar dielectric properties and PCE, these materials have many attractive properties, such as ambipolar charge‐transport properties, limited charge recombination, tunable bandgap, recyclable dissolution–recrystallization, flexible and printable, and wonderful nonlinear optical properties .…”
Section: Introductionmentioning
confidence: 99%